1998
DOI: 10.1097/00000542-199801000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a Cerebral Oximeter in Healthy Volunteers under Conditions of Isocapnic Hypoxia 

Abstract: During isocapnic hypoxia in healthy persons, cerebral oxygenation as estimated by near infrared spectroscopy precisely tracks changes in measured S(jv)O2 within individuals, but the relation exhibits a wide range of slopes and intercepts. Therefore the clinical utility of the device is limited to situations in which tracking trends in cerebral oxygenation would be acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(55 citation statements)
references
References 30 publications
4
48
0
3
Order By: Relevance
“…17 Pollard et al 6 showed that cerebral NIRS oximetry reflected cerebral oxygenation in an AV-ratio of 0.25 in healthy adult volunteers. This fixed AV-ratio is widely accepted in literature, although some studies suggest wide interindividual variation.…”
Section: Reactivity Of Cerebral Nirs Oximetry Assuming a Fixed Av-ratiomentioning
confidence: 99%
“…17 Pollard et al 6 showed that cerebral NIRS oximetry reflected cerebral oxygenation in an AV-ratio of 0.25 in healthy adult volunteers. This fixed AV-ratio is widely accepted in literature, although some studies suggest wide interindividual variation.…”
Section: Reactivity Of Cerebral Nirs Oximetry Assuming a Fixed Av-ratiomentioning
confidence: 99%
“…NIRS measurements have been well correlated with intracellular O 2 tension in muscle (38) and venous O 2 saturation in both muscle (14) and cerebral tissue (20). However, the relative contribution of skin blood flow to NIRS tissue signals has been questioned because NIRS probes are typically placed on the skin surface.…”
Section: Limitations Of the Study And Technical Considerationsmentioning
confidence: 99%
“…Cerebral spectroscopy has been shown to track changes in jugular venous bulb saturations in healthy volunteers under conditions of isocapnic hypoxia (12) and has also been validated by comparison with PET scanning, with 133 Xe washout methods and with internal carotid artery stump pressures (54). We have used this technique during dynamic studies of cerebral oxygenation at altitude and assessed the effects of hyperventilation, oxygen therapy, and CO 2 supplementation (19,20) and during assessment of the effects of pressurization in a portable hyperbaric chamber (21).…”
mentioning
confidence: 99%